Simultaneous radicular cyst and mucoepidermoid carcinoma in the maxilla: a diagnostic nightmare. (12th June 2013) - Nabil, Syed; Lo, Regina Cheuk Lam; Choi, Wing Shan
Abstract : We present a case of a 20-year-old woman presenting initially with an asymptomatic palatal swelling. Radiographic examination showed a cyst at the right maxilla with bucco-lingual expansion and perforation of palatal bone. Incisional biopsy was carried out via a buccal approach and the result revealed a benign odontogenic cyst, in keeping with radicular cyst. The patient was then scheduled for cyst enucleation. During the procedure, it was found that the palatal lesion was unrelated to the maxillary cyst. Incisional biopsy of the palatal mass was carried out and revealed a low-grade mucoepidermoid carcinoma. The patient then had a partial maxillectomy with fibula flap reconstruction. There was no recurrence at postoperative 1 year follow-up and she was rehabilitated with dental implants.